Extreme sexual dimorphism and polymorphism in two species of the tiger moth genus Dysschema (Lepidoptera: Erebidae): association between males and females, sexual mimicry and melanism revealed by integrative taxonomy. Issue 3 (4th May 2017) - Moraes, SimeÃo De Souza; Cardoso, Lucas Waldvogel; Silva-brandÃo, Karina Lucas; Duarte, Marcelo
Abstract : The genus Dysschema belongs to Pericopina (Erebidae: Arctiinae: Arctiini). It is outstanding because of the extreme sexual dimorphism and polymorphism found among many of its species, with males and females mimicking different groups within Lepidoptera. This has led to a confused taxonomic scenario because males and females were routinely described as different species, and an inflated number of species was established. Dysschema maginata and D. terminata are sexually dimorphic, the females of both species have the same wing pattern and represent a rare case of sex-limited mimicry. Both species were described based on the females, and the association with males was proposed long after the original descriptions without any further evidences. Despite these similarities, the former species represents a simple dual case of polymorphism, while the latter species represents an uncommon case of multiple-dual polymorphism with at least four phenotypes for the male. In this study, we tested and corroborated hypothesized associations between sexes of D. marginata and D. terminata using DNA barcodes. The morphological studies also corroborated four phenotypes of males in D. terminata, with a new synonym: Dysschema Hering, 1928 and the the first record of a female-like male morph in a population of a sexually dimorphic species in Arctiinae. Moreover, we redescribed the two species, with comments on morphology and discussion on the polymorphism. A lectotype is designated for Pericopis holofernes Butler, 1871, synonym of D. terminata, to ensure the stability of the name.